When Science Counts as Much as Reading and Mathematics: An Examination of Differing State Accountability Policies - Judson, Eugene (Education Policy Analysis Archives, 2012)
Although only results from mathematics and reading assessments are required to be used when Adequate Yearly Progress (AYP) of schools is calculated, some states have elected to include science achievement results either in their AYP calculations or as part of a separate dual accountability system. This study examined 2009 National Assessment for Educational Progress (NAEP) results based on how states use, or do not use, science in their accountability programs. Consideration was given to the idea that including science achievement might detract from efforts, and consequently results, in mathematics and reading. Results from both fourth- and eighth-grade data indicated that states choosing to use science in their accountability calculations did not lose ground in those other subjects. Fourth-grade data indicates that the states using science in their accountability programs additionally had significantly higher science achievement than the other states.